Epidermoid cyst arising from the epididymis in a prepubertal boy - Kenji Tsutsui; Fumi Matsumoto; Takashi Ueno; Yuko Ueda; Satoko Matsuyama; Futoshi Matsui (Urology Case Reports, 2025)
Benign epididymal neoplasms are rare in children. While epidermoid cysts commonly occur in the testis, scrotum, and foreskin, they are only rarely found in the paratesticular region. We present the first reported case of an epidermoid cyst arising from the epididymis in a 3-year-old boy. Testis-sparing surgery was performed to obtain a definitive diagnosis.